Institutional differences and the development of entrepreneurial ventures: A comparison of the venture capital industries in Latin America and Asia - Bruton, Garry D; Ahlstrom, David; Puky, Tomas (Journal of International Business Studies, 2009)
This paper examines how differences in distinct institutional clusters of countries impact on the vital entrepreneurial activity of venture capital, and how individuals, organizations, and their collective action in turn shape those institutions. The focus on venture capital offers researchers the opportunity to view an industry that comes from a common root, with strong and consistent traditions, in which to examine how the differing institutional settings impact on behaviors in different markets, and how the institutions themselves may change in these settings. We also focus on emerging economies, since such economies offer a natural laboratory to study the impact of institutional change. Specifically, this paper employs an institutional theory perspective to examine venture capital in two regions of the world that form institutional clusters of countries – Latin America and Asia. It is found that the venture capital industry exhibits a strong consistency across many dimensions; yet institutions in these two distinct settings result in significant differences in industry practice. Therefore this research is able to contribute to both empirical and theoretical understanding of emerging economies, institutions in those environments, and venture capital.